Decision Support System for Determining Thesis Supervisor using A Weighted Product (WP) Method - Arifin, Suci Ramadhani; Mintamanis, Josua Crishan (JOIN (Jurnal Online Informatika), 2018)
English Department of Tadulako University is a department with the highest number of lecturers in Tadulako University. Thesis supervisor determination at the English Department of Tadulako University still use the conventional way so that the determination of the thesis supervisor is done in a long time. In addition, some lecturers have more workload than other lecturers. Decision support system for the determination of the thesis supervisor in the English Department of Tadulako University was built to overcome this problem using the Weighted Product method. The system is a desktop-based application using the Visual Studio programming language and MySQL DBMS for database processing. The application of a decision support system for determining thesis supervisors can help make the selection of supervisors accurately and quickly with a mathematical calculation system.